Pandemic within workplaces. Address the recovery post Covid-19 by training - Biasin, Chiara; Marin, Veronica (Form@re - Open Journal per la formazione in rete, 2021)
This paper concerns the effects of the pandemic in the Italian working context. The Covid-19 crisis has forced transformations in working methods, has involved changes of working spaces and times, has generated new social and professional needs and different training demands. The aim is to understand how Covid-19 has changed the way people work and stay at work, exploring the effects of the pandemic in new skills and training needs of adults at work. Through a quantitative approach, an organization in the North-East of Italy is studied as a case study in order to offer theoretical perspectives and practical advice useful to broaden the discussion on the topic. Pandemia e mondo del lavoro: sostenere la ripresa attraverso la formazione. Questo contributo riguarda gli effetti della pandemia nel contesto lavorativo italiano. Il Covid-19 ha imposto trasformazioni nelle modalità lavorative, ha implicato ristrutturazioni degli spazi e dei tempi di lavoro, ha generato nuovi bisogni sociali e professionali e nuove domande formative. L’obiettivo di questo articolo è quello di comprendere come e in che modo il Covid-19 abbia cambiato il modo di fare e di stare al lavoro, facendo emergere nuove competenze e differenti bisogni formativi presso gli adulti al lavoro. Attraverso un approccio di tipo quantitativo, verrà studiato come caso di ricerca una azienda del Nord Est, al fine di offrire prospettive teoriche e indicazioni pratiche utili per una più ampia discussione sul tema.